Forming a Competence Model in the Course of Volunteer Activities of Students to Include Them into the Organization’s Personnel Reserve - V. Vinichenko, Mikhail; L. Сhulanova, Oksana; V. Bolotov, Svyatoslav; V. Melnichuk, Alexander; A. Melnichuk, Yuliya (International Journal of Engineering and Technology, 2018)
The article deals with the issue of using the volunteer movement to improve the efficiency of organizations due to the innovative model of the personnel reserve formation. The comprehensive use of sociological and statistical methods based on the focus group and questionnaire survey allowed creating the desired competence model of volunteer students to include them in the personnel reserve of organizations, and then offering an acceptance competencesâ€™ model of socially oriented volunteer students that would allow including them in the personnel reserve of the organization and assign career development vectors. In consequence of research it was established that when including volunteer students into personnel reserve, experts in the field of personnel management should reveal in candidates various competences such as emotional competence, teamwork skills, and knowledge of health protection principles which allowed uncovering creative potential of volunteer students, their aspiration to serve society and as a consequence â€“ to develop a brand, and increase competitiveness of the company. When entering volunteer students into the personnel reserve list of a particular company, it is necessary to determine the permissible level of noncompliance of competences with the specified indicators at a rate of not more than 50%. The proposed model can serve as a basis for the effective use of the volunteer studentsâ€™ potential when put on the list of the company personnel reserve.Â